Seismic Performance of Reinforced Concrete Buildings in Darchula, Nepal: A Fragility-Based Approach - Bohara, Birendra Kumar; Abdellatif, Benbokhari; Deupa, Jyoti; Mani Joshi, Nirmal; Jagari, Sangam (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2025)
This research evaluated the seismic vulnerability of non-engineered reinforced concrete (RC) buildings compared with that of engineered RC structures in the Darchula region of Far-Western Nepal, an area prone to high seismic risk. This study emphasizes the seismic performance of buildings under various loading conditions by examining construction practices and identifying structural deficiencies in RC buildings in Darchula, Nepal. Linear elastic and nonlinear pushover analyses are used to assess periods, mass participation, base shear, inter-story drift, capacity curves, nonlinear drift demand, and fragility curves. Models designed according to national and international standards are compared with non-engineered buildings (S1 – S6) to highlight the discrepancies in seismic resilience. The study further provides a probabilistic fragility framework to quantify damage likelihood at varying seismic demand levels. The results show that engineered buildings exhibit significantly greater resistance to seismic forces, with greater flexibility and higher base shear capacities. In contrast, non-engineered buildings, particularly shorter structures, are more prone to damage under moderate seismic events. Research indicates that ground floors in non-engineered buildings consistently exhibit the most significant inter-story drift as a result of softstory impacts, highlighting them as crucial failure points. Fragility curves derived from spectral displacement values reveal that non-engineered buildings reach critical damage states at lower levels of seismic demand, indicating greater vulnerability. This research underscores the importance of enforcing seismic design standards and retrofitting non-engineered buildings to improve their earthquake resilience in seismic hotspots such as Darchula, Nepal. These findings provide a foundation for future seismic risk reduction strategies and highlight the urgent need for improved building practices to mitigate earthquake-related damage.